Spatial memory training in a citizen science context. - Palermo, Eduardo; Laut, Jeffrey; Nov, Oded; Cappa, Paolo; Porfiri, Maurizio (Computers in Human Behavior, 2017)
Memory deficit is one of the primary effects of intellectual disability, and has a great impact on daily life. Here, we propose a novel spatial memory training system based on a citizen science virtual environment, in which users navigate an aquatic robot in a polluted canal and identify specific objects from images acquired by the robot. A portable low-cost electroencephalography device is utilized to enhance the degree of interactivity and enable real-time estimation of the affective state of the user. We involved a cohort of 60 healthy adult subjects to evaluate users' interest, memory performance, and affective variables as a function of navigation modality (active versus passive) and interface (a traditional computer mouse versus the headset). Despite offering a higher level of difficulty, the headset was preferred over a traditional mouse control by the users, whose spatial memory performance did not vary with the navigation modality or the interface. Active navigation was found to lead to a higher level of engagement, as measured by the headset. These findings suggest the possibility of a new, effective, and entertaining form of intellectual rehabilitation with potential impact on fetal alcohol syndrome.